IMMISCIBILITY OF ALUMOSILICATE-ALKALI ALUMOFLUORIDE MELTS IN THE LIQUIDUS ZONE (EXPERIMENTAL DATA) - Gramenitskiy Ye.N.; Shchekina T.I.; Mitreykina O.B. (My University, 1989)
The alkali-alumosilicate system consisting of albite, orthoclase, quartz and water has long been used as a simplified model granite system. Crystallization of granitic magma leaves the residual melt richer in volatile and salt components. This is what constitutes crystallization-induced differentiation in granite. Systems with the above components are particularly important for an understanding of the concluding stages of magma crystallization. Interesting calculations and model experiments demonstrating the complexity of phase relationships in the residual melts that were enriched in volatile and salt components as a result of differentiation were made 40 years ago by F.G. Smith. A decrease in the temperature transforms this type of liquid immiscibility-induced separation into an alumosilicate-salt separation, which was known previously. Mutually immiscible melts similar to those obtained in the authors' experiments at 800°C have been found in inclusions of spherical granites of the Kent body in central Kazakhstan, which will be described in a separate paper.